PERAN PENDIDIKAN ISLAM DALAM MEMBENTUK KARAKTER SISWA DI ERA REVOLOSI INDUSTRI 4.0 DI MADRASAH TSANAWIYAH NEGERI 1 BANYUMAS - Tutuk Ningsih (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
The role of Islamic education is a very strong foundation and becomes a reference of developing students’ character to face the Industrial Revolution 4.0 Era, and Islam is a source of truth and strength that can deliver ways on daily lives to achieve human character formation. Therefore, Islamic education is an important part of preparing the quality students. In other words, Islamic Education has a major contribution in the process of building students who have good character, have the ability to compete in the industrial revolution 4.0 era, have the ability to use global technology, and have the ability to adapt to the rapid development of technology. Islamic education is also expected to facilitate students to study hard consistently in order to face this era and students are expected to master sophisticated global technology without limits. This study aims to describe and analyze the role of Islamic Education in building students’ character in the Industrial Revolution 4.0 era. To achieve the purposes of the study, this study used a qualitative method with a qualitative-naturalistic approach. Various data collection techniques used in this study are observation, in-depth interviews, and documentation. The results shows that the role of Islamic Education in building students' character was carried out through the following activities; 1) Intra-curricular activities: in this activity, the teacher inserts characters in the teaching and learning process of all subjects namely Qu'ran hadith, Fiqh, History of Islamic Culture, Arabic, and Aqeedah Akhlak. The teacher connects directly with material of akhlaq or character 2) Extra-curricular activities include: Tilawatil Qur'an (reading the Qur'an) using digital literacy methods, Tahfidzul Qur'an (memorizing the Qur'an), Qitobha, Hadroh (Islamic Music) and Calligraphy. Through these two types of activities built several characters: religious, honest, fond of reading, responsible, independent, appreciating achievements, caring socially and hard work. By having the character, the students are ready to face the industrial era 4.0.